2011
DOI: 10.5296/ber.v2i1.1152
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of the Stock Market Index for a Major Latin American Country and Policy Implications

Abstract: Applying the exponential GARCH model and based on a quarterly sample during 1998.Q1-2011.Q2, we find that the Argentine stock market index is positively associated with real GDP, the ratio of M2 money supply to GDP, the peso/USD exchange rate and the U.S. stock market index. It is negatively influenced by the money market rate, government spending as a percent of GDP and the inflation rate. Hence, a strong domestic economy, a lower interest rate, an increased money supply as a percent of GDP, lower government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
14
0
4
Order By: Relevance
“…(2012) and Makan et al (2012) used the VECM to model the relationship between the stock prices and macroeconomic variables and, hence, a long-run equilibrium relationship exists between them. Hsing and Budden (2012) applied the exponential GARCH model and found that the Argentine stock market index is positively associated with real GDP, the ratio of M2 money supply to GDP, the peso/USD exchange rate and the U.S. stock market index. Bekhet and Matar (2013) found the existence of a long-term equilibrium relationship between the Stock Price Index and the macroeconomic variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2012) and Makan et al (2012) used the VECM to model the relationship between the stock prices and macroeconomic variables and, hence, a long-run equilibrium relationship exists between them. Hsing and Budden (2012) applied the exponential GARCH model and found that the Argentine stock market index is positively associated with real GDP, the ratio of M2 money supply to GDP, the peso/USD exchange rate and the U.S. stock market index. Bekhet and Matar (2013) found the existence of a long-term equilibrium relationship between the Stock Price Index and the macroeconomic variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4.Abugri (2008) and Hsing, Budden and Phillips (2011) suggest that macro- economic variables, such as inflation and the risk-free rate are important determinants of stock returns for Latin American countries.…”
mentioning
confidence: 99%
“…7. Abugri (2008) and Hsing et al (2012) suggest that macroeconomic variables, such as inflation and the risk-free rate, are important determinants of stock returns for Latin American countries.…”
Section: Notesmentioning
confidence: 99%